Analisis Mutu Ikan Lele (Clarias batrachus) Asap Produksi Rakyat di Jalan Lintas Musi II Desa Keramasan, Kertapati, Palembang - Firnanda Citra; Kiki Yuliati; Ace Baehaki (Jurnal FishtecH, 2015)
The purpose of this research was to analize the quality of smoked catfish sold at Musi Dua street data were obtained through and series of survey. The smoke fish processing staser were material of supply, clear of weeds, washing of fish, work with salt and furnigation. Furnigation was a process in very important because can be specific character of smoke fish in the production. The result of the microbiology smoke catfish with sampling showed average be able to 1.8x106, 1.7x106 and 1.65x107. The result of the chemistry analysis smoke catfish showed in water activity of testing was about 0.84. The result standard water of testing showed smoke catfish was about 46.8% until 48.8% for every sample.